Histologic transformation of epidermal growth factor receptor–mutated lung cancer. (May 2022) - Fujimoto, Daichi; Akamatsu, Hiroaki; Morimoto, Takeshi; Wakuda, Kazushige; Sato, Yuki; Kawa, Yoshitaka; Yokoyama, Toshihide; Tamiya, Motohiro; Hiraoka, Ryota; Shingu, Naoki; Ikeda, Hideki; Tamiya, Akihiro; et al.
Abstract: Purpose: This study aimed to determine the incidence and clinical course of epidermal growth factor receptor ( EGFR )-mutated lung cancer with histologic transformation (HT). Patients and methods: We conducted a multicentre, retrospective, cohort study of patients with advanced EGFR -mutated lung cancer who received EGFR-tyrosine kinase inhibitors (TKIs) between 2012 and 2019. The primary outcome was the incidence of HT. The secondary outcome was treatment efficacy in patients with HT. Results: In total, 6356 patients were enrolled. In 2624 patients, the histological type was proven by rebiopsy after acquiring resistance to EGFR-TKIs. Among them, 74 patients had HT (incidence rate: 2.8% [95% confidence interval: 2.3%–3.5%]). The median progression-free survival after EGFR-TKIs and first-line therapy after confirming HT was 10.4 and 4.4 months, respectively, which was not significantly different between patients with transformation to high-grade neuroendocrine carcinoma and those with transformation to another subtype of non–small cell lung cancer. Overall survival after confirming HT was 12.2 months. Twenty-seven patients received immune checkpoint inhibitors: 6 and 21 received immune checkpoint inhibitors before and after confirming HT, respectively. No patients achieved 1-year progression-free survival. The median progression-free survival after immune checkpoint inhibitor therapy after confirming HT was 1.6 months. Conclusion: HT occurred in approximately 3% of EGFR -mutated patients who developed resistance to EGFR-TKIs. Cytotoxic agents are likely to be effective in patients with HT. However, the therapeutic effectiveness of immune checkpoint inhibitors was limited in these patients. Given the rarity of HT and absence of prospective trials, our findings are important to inform the treatment of these patients. Highlights: This is the largest EGFR -mutated lung cancer retrospective cohort study. We analysed 74 patients with histologic transformation (HT). The incidence rate of HT was lower (2.8%) than previously reported. Cytotoxic agents are likely to be effective in patients with HT. None of the patients achieved 1-year PFS with immune checkpoint inhibitor therapy.